New Trends in Network Security and Precautions - Xiang, Jun (Journal of Theory and Practice of Engineering Science, 2025)
With the continuous development of network information technology in China, the incidence of computer network security problems is also getting higher and higher. Once the computer appears network security problems will directly affect people's normal life and production. Therefore, computer users need to have a strong awareness of network security management, take effective measures to prevent computer network security problems, and reduce the incidence of computer network security problems.